Intelligent robotics and applications 5th International conference, ICIRA 2012, Montral, Canada, October 3-5,2012, Proceedings, Part I - Rakheja, Subhash; Liu, Honghai; Su, Chun-Yi (Lecture Notes in Computer Science, 2012)
The three volume set LNAI 7506, LNAI 7507 and LNAI 7508 constitutes the refereed proceedings of the 5th International Conference on Intelligent Robotics and Applications, ICIRA 2012, held in Montreal, Canada, in October 2012. The 197 revised full papers presented were thoroughly reviewed and selected from 271 submissions. They present the state-of-the-art developments in robotics, automation and mechatronics. This volume covers the topics of adaptive control systems; automotive systems; estimation and identification; intelligent visual systems; application of differential geometry in robotic mechanisms; unmanned systems technologies and applications; new development on health management, fault diagnosis, and fault-tolerant control; biomechatronics; intelligent control of mechanical and mechatronic systems.